Genomic ancestry and the social pathways leading to major depression in adulthood: the mediating effect of socioeconomic position and discrimination - Loret de Mola, Christian; Hartwig, Fernando Pires; Gonçalves, Helen; Quevedo, Luciana de Avila; Pinheiro, Ricardo; Gigante, Denise Petrucci; Motta, Janaína Vieira dos Santos; Pereira, Alexandre C.; Barros, Fernando C.; Horta, Bernardo Lessa (BMC psychiatry, 2016)
Evidence suggests that there is an association between ethnicity/skin color and depression; however, many contextual and individual variables, like sense of discrimination and socioeconomic position (SEP), might influence the direction of this association. We assessed the association between African ancestry and major depression among young adults that have been followed-up since birth in a Southern Brazilian city, and the mediating effect of SEP and discrimination. In 1982, all hospital deliveries in Pelotas (Southern Brazil) were identified; liveborns were examined and their mothers interviewed (n = 5914). In 2012-13, at 30 years of age, we used the Mini International Neuropsychiatric Interview (MINI) for major depression diagnosis. In addition, DNA samples were genotyped for approximately 2.5 million single nucleotide polymorphisms (SNPs) using Illumina (CA, USA) HumanOmni2.5-8v1 array. Genomic ancestry estimation was based on approximately 370 000 single nucleotide polymorphisms (SNPs) mutually available for the Pelotas cohort and selected samples (used as reference panels) of the HapMap and Human Genome Diversity (HGDP). We estimated prevalence ratios (PR) using Poisson regression models and evaluated the association between percentage of African ancestry and major depression. We used G-computation for mediation analysis. At 30 years, 3576 individuals were evaluated for major depression (prevalence = 7.9 %). Only individuals in the highest SEP, who had a percentage of African ancestry between >5-30 % and >30 % had a prevalence of major depression 2.16 (PR = 2.16 95 % CI [1.05-4.45]) and 2.74 (PR = 2.74 95 % CI [1.06-7.06]) times higher, than those with 5 % or less, respectively. Among these subjects, sense of discrimination by skin color, captured 84 % of the association between African ancestry and major depression. SEP is an important effect modifier of the positive association between African ancestry and major depression. In addition, this association is predominantly mediated by the sense of feeling discriminated by skin color.